Basicity determination of SBA-15 doped with different alkaline metals through CO2 adsorption and isopropanol decomposition - Reale, Natalia Romina; Cagnoli, Maria Virginia (European Journal of Chemistry, 2020)
In order to increase the activity and selectivity towards to light olefins in the Fischer-Tropsch synthesis, new support for the role of iron (Fe) are presented. Thus, SBA-15 was synthetized and doped with different alkaline metals preserving the structural characteristics of the mesoporous solid. The samples were characterized by X-ray diffraction at low angles, N2 adsorption, atomic absorption spectroscopy, CO2 desorption at programmed temperature and isopropanol test. The alkaline metals (Li, K and Cs) introduction into the channels of the solid, generate basic sites of different strength that are not present in the SBA-15 without doping and do not produce significant changes in the structural and textural properties of the SBA-15, only a densification in the walls of the channels is evidenced. According to the alkaline metal used and through CO2 adsorption and isopropanol decomposition, it was possible to established the order by the total number of sites: Li >> K » Cs, and the force order for both types of sites (weak and intermediate): Li > Cs > K.